Cover crops shape the soil bacterial community in a tropical soil under no-till - Leite, Hugo Mota Ferreira; Calonego, Juliano Carlos [UNESP]; Rosolem, Ciro Antonio [UNESP]; Mendes, Lucas William; de Moraes, Leonardo Nazario [UNESP]; Grotto, Rejane Maria Tommasini [UNESP]; Araujo, Fabio Fernando; Pereira, Arthur Prudencio de Araujo; Melo, Vania Maria Maciel; Araujo, Ademir Sergio Ferreira (Elsevier, 2021)
The introduction of cover crops in tropical cropping systems under no-till (NT) is paramount for improving the chemical and physical properties of the soil as well as the sustainability of the system. Soil carbon is increased under cover crops, and the soil microbiota is undoubtedly modified. However, the effects of different cover crops on the abundance and structure of the soil bacterial community remain unclear. Therefore, this study used 16S rRNA sequencing to assess the abundance and structure of the bacterial community in a crop rotation system under NT using the following cover crop species: pearl millet (Pennisetum glaucum), grain sorghum (Sorghum bicolor), and Sunn hemp (Crotalaria juncea). For comparison, one additional treatment was kept under bare fallow. Soil samples were collected to a depth of 10 cm to assess the bacterial community. Redundancy analysis (RDA) showed that the bacterial community was correlated with microbial biomass N under millet, ammonium under Sunn hemp, and soil base saturation and P under sorghum and fallow. The most abundant phyla were Actinobacteria, Proteobacteria, and Chloroflexi under millet, Chloroflexi and Latescibacteria under Sunn hemp, and Proteobacteria and Patescibacteria under sorghum. Co-occurrence network analysis showed that the complexity of the bacterial community was highest under millet, followed by fallow, Sunn hemp, and sorghum. In summary, this study shows that cover crop species specifically shape microbial community structure and networks, with changes in the abundance of bacterial groups related to soil quality and health.
Keywords: 16S rRNA sequencing; Soil microbial ecology; Sustainable system